Peg + Cat. Chickens on the loose, and other really big problems! [videorecording (DVD)] ([Publisher not identified], 2014)
Follow the adorable, spirited Peg and her sidekick Cat as they embark on adventures, solve problems together, and learn foundational math concepts and skills. In each episode, Peg and Cat face a really big problem, a messy funny crisis they must somehow solve without totally freaking out! This DVD features eight fun-filled adventures.